Photocontrolled DNA Binding of a Receptor-Targeted Organometallic Ruthenium(II) Complex - Barragán, Flavia; López-Senín, Paula; Salassa, Luca; Betanzos-Lara, Soledad; Habtemariam, Abraha; Moreno, Virtudes; Sadler, Peter J; Marchán, Vicente (Journal of the American Chemical Society, 2011)
A photoactivated ruthenium(II) arene complex has been conjugated to two receptor-binding peptides, a dicarba analogue of octreotide and the Arg-Gly-Asp (RGD) tripeptide. These peptides can act as “tumor-targeting devices” since their receptors are overexpressed on the membranes of tumor cells. Both ruthenium–peptide conjugates are stable in aqueous solution in the dark, but upon irradiation with visible light, the pyridyl-derivatized peptides were selectively photodissociated from the ruthenium complex, as inferred by UV–vis and NMR spectroscopy. Importantly, the reactive aqua species generated from the conjugates, [(η6-p-cym)Ru(bpm)(H2O)]2+, reacted with the model DNA nucleobase 9-ethylguanine as well as with guanines of two DNA sequences, 5′dCATGGCT and 5′dAGCCATG. Interestingly, when irradiation was performed in the presence of the oligonucleotides, a new ruthenium adduct involving both guanines was formed as a consequence of the photodriven loss of p-cymene from the two monofunctional adducts. The release of the arene ligand and the formation of a ruthenated product with a multidentate binding mode might have important implications for the biological activity of such photoactivated ruthenium(II) arene complexes. Finally, photoreactions with the peptide–oligonucleotide hybrid, Phac-His-Gly-Met-linker-p5′dCATGGCT, also led to arene release and to guanine adducts, including a GG chelate. The lack of interaction with the peptide fragment confirms the preference of such organometallic ruthenium(II) complexes for guanine over other potential biological ligands, such as histidine or methionine amino acids.